Middle Bronze Age II Pottery Kiln at Oylum Höyük - Sabahattin Ezer (Belleten)

(untitled)
Despite the newly acquired information with increasing studies in Türkiye, archaeological evidence regarding ceramic production in some regions and periods is still not sufficient. Although our knowledge about prehistoric and protohistoric pyrotechnology increases, we can currently say little about the size of ceramic production, the settlement and regional density of pottery kilns, their distribution, development and contexts, in short their roles. The pottery kiln discovered at Oylum Höyük in 2020 and dated to Middle Bronze Age II is in good physical condition compared to its contemporaries in Anatolia, Mesopotamia, and the Levant. Oylum Höyük kiln is currently the best documented MBA kiln in Türkiye. Therefore, all its technological features could be identified, revealing valuable information for understanding pottery kiln technology and development. The kiln, consisting of three parts including ash pit, combustion chamber and firing chamber, can be described as an updraught kiln with an arched combustion chamber and a firing chamber with circular plan. Extensive data from the MBA pottery kilns unearthed in the Levant allows us to compare the Oylum Höyük kiln with its contemporaries and to conclude that it is typologically and technologically closer to the Levant kilns. The area, which was represented in the MBA I by a monumental structure probably with administrative function, started to be used as an industrial production site with several pyrotechnic installations in the early phase of MBA II. We can say with certainty that there was a radical change in the settlement organization.